Guyana : technical assistance needs for democracy and sustainable development 1994-1997 (Minstry of Foreign Affairs GeorgetownGY, 1994)
Reviews the performance and constraints of the Guyanese economy. Seeks to indicate to multilateral and bilateral donors the areas that require further technical assistance in order to improve basic amenities and expand investment opportunities as well as to sustain the economy on a developmental course.
Contents: v.1. Background and assessment. - v.2. Profiles of technical assistance projects